Subliminal mortality salience does not increase physical strength output in double-blind randomized controlled trial - Bartenschlager, Christopher T. J.; Jansen, Petra (Frontiers in Psychology, 2023)
Introduction: Using the morality salience paradigm, this research tested whether subliminal death stimuli lead to increased physical strength. Moreover, it was investigated if mindfulness and self-esteem instability influence terror management.Methods: In total, data from 160 undergraduate sports students were analyzed. Participants completed a word decision task in which they were presented with either the word death or pain for 28.5ms. Before and after the task, their grip strength was measured using a hand dynamometer.Results: Linear mixed models could neither confirm the effect of the mortality salience hypothesis on strength nor an influence of mindfulness and self-esteem.Discussion: The results raise the question of a potential influence of subliminal mortality salience on athletic performance and how mindfulness and self-esteem instability affect terror management.